Moving from Histopathology to Molecular Tools in the Diagnosis of Molluscs Diseases of Concern under EU Legislation - Aranguren, Raquel; Figueras, Antonio (Frontiers in Physiology, 2016)
One of the main factors limiting molluscs production is the presence of pathogens and diseases. Disease agent transfer via transfers of live molluscs has been a major cause of disease outbreaks and epizootics. Because of that, the European Union has adopted several decisions and directives, the last in 2006 (2006/88/EC) to control movements of marine organisms over the European countries. Once the disease is established in a determined area its eradication is a complicated task because life cycle of pathogens are not completely known and only a good and early diagnosis of the disease could be the most appropriate way to deal with it. Besides, molluscs do not have an adaptive immune response and vaccination strategies are not possible Molluscs listed diseases under EU legislation are mainly protozoan parasites, that’s why histological techniques are recognized for their diagnosis. However, molecular techniques are being increasingly used primarily as confirmatory techniques of the presence of the pathogens but also in disease monitoring programs. Research perspectives are mainly focussed in the optimization, of the already described techniques to gain in sensitivity and sensibility and in the development of new molecular biology techniques (quantitative real time PCRs), that are faster and easier to apply and that allow a positive diagnosis even in early stages of infection. However, molecular tools detect DNA sequences of the pathogen which does not imply that pathogen is viable in the cell host and the infection is established. Consequently, it needs to be validated against other techniques, such as histology or in situ hybridization, so that its reliability can be determined.